The role of psychoeducation in the treatment of schizophrenia - Paszkiewicz-Mes, Emilia (Nursing in the 21st Century, 2013)
PSYCHOEDUCATION IN THE TREATMENT OF SCHIZOPHRENIA Schizophrenia is a chronic disease, with periods of acute illness and of remission. It is characterized by diversified course and clinical presentation, symptoms of mental disintegration and the risk of maladjustment. Even in case of applying optimal medicine and optimal doses, pharmacotherapy is not the sufficient protection against a relapse. The therapy of sick people should include varied influences, such as biological methods, sociotherapy, psychotherapy and rehabilitation. Psychoeducation of both patients and their families is also a very important element in the therapy of schizophrenia. Good contact with the family has an impact on the effective process of treatment. Participation of patients and their families in psychoeducation affects reducing the frequency of the hospitalization and extending periods of remission. It contributes to the improvement of cooperation with the treated patient, increases the adherence to medical recommendations and improves the quality of patient’s life. The concept of psychoeducation is to transmit the knowledge of the disease, treatment and recognition of symptoms and relapses of the disease, and also to develop the plan of therapy in such situations. The sense of psychoeducational programs is unquestionable, therefore, the aim is to present the assumptions and the analysis of the impact of psychoeduacation on the process of patient’s treatment.